72.7k views
4 votes
1. Solve the system of equations
-x+y=0
4x - 3y=-3
I
=

1 Answer

3 votes

Answer:

x = -3

y = -3

Explanation:

To solve this system of equations, you can use the elimination method, which is to have one of the variables match, but be the opposite sign of the other:

- x + y = 0

4x - 3y = -3

The easier one to match is the 1st equation, and to make it match oppositely, you multiply the whole equation by 4:

4(-x + y = 0)

-4x + 4y = 0

4x - 3y = -3

-4x and 4x cancel each other out:

4y = 0

-3y = -3

_______

y = -3

Then plug in -3 for y, into one of the equations:

- x + y = 0

- x - 3 = 0

Add 3 to both sides:

- x = 3

Divide both sides by -1:

x = -3

User Jerry Wu
by
6.3k points